IMPLEMENTASI APLIKASI TOKO ONLINE GANGER UNTUK PENDAUR ULANG SAMPAH BERBASIS WEB DI TASIKMALAYA - Andi Nur Rachman; Cecep Muhamad Sidik Ramdani; Euis Nur Fitriani Dewi (Universitas Islam Indonesia, 2020)
Currently in 2018 Indonesia's creative industry is growing rapidly with evidence of the emergence of start-ups and companies of the nation's work more and more popping up as well as GoJek, BukaLapak and others. The community is also very supportive of this, seen from the number of users on each of these platforms. This can conclude that the Indonesian people today prefer facilities that are efficient, fast and inexpensive. Therefore the Digitat company has a wide market in Indonesia. These problems such as economic and waste issues, Garbage Ranger or abbreviated as GANGER present as an application that can be a link between buying and selling providers or waste management and recycling business, becoming a place of buying and selling between consumers and recycling businesses, being a provider of information on product manufacturing -products from trash and waste pricing information providers.